When Myocardial Injury in Lupus Is Not Lupus: Probable Antimalarial‐Associated Cardiomyopathy Mimicking Lupus Myocarditis - Diego Armando Pérez Covo; María Camila Bernal Beltrán; Diego Alejandro Ortega; Cristian Orlando Porras Bueno; Emilio José Juan Guardela; Carlos Hernán Calderón; Edward Andres Cáceres Méndez; Laura Valentina Omaña Álvarez; Alejandro Mariño Correa; Ángel Alberto García Peña (Clinical Case Reports, 2026)
ABSTRACT Antimalarial cardiotoxicity may mimic lupus myocarditis in systemic lupus erythematosus. We report a 53‐year‐old woman with chronic antimalarial exposure, myocardial injury, biventricular dysfunction, electrical abnormalities, low lupus activity, and no myocardial edema. Chloroquine withdrawal was followed by clinical improvement and left ventricular function recovery, supporting probable antimalarial‐associated cardiomyopathy.